Incorporation of Organic Growth Additives to Enhance In Vitro Tissue Culture for Producing Genetically Stable Plants - Hamdeni, Imtinene; Louhaichi, Mounir; Slim, Slim; Boulila, Abdennacer; Bettaieb, Taoufik (MDPI, 2022)
The growing demand for native planting material in ecological restoration and rehabilitation for agro-silvo-pastoral ecosystems has resulted in a major global industry in their sourcing, multiplication, and sale. Plant tissue culture is used for producing high-quality, disease-free, and true-to-type plants at a fast rate. Micropropagation can help to meet the increasing demand for planting material and afforestation programs. However, in vitro plant propagation is an expensive technique compared to conventional methods using suckers, seeds, and cuttings. Therefore, adopting measures to lower production costs without compromising plant quality is essential. This can be achieved by improving the culture media composition. Incorporating organic growth additives can stimulate tissue growth and increase the number of shoots, leaves, and roots in culture media. Organic growth supplementation speeds up the formation and development of cultures and yields vigorous plants. Plant regeneration from meristems (shoot tips and axillary buds) is a reliable way to produce true-to-type plants compared with callus and somatic embryogenesis regeneration, but in vitro culture environments can be mutagenic. Therefore, detecting somaclonal variations at an early stage of development is considered crucial in propagating plants. The genetic stability of in vitro regenerated plants needs to be ascertained by using DNA-based molecular markers. This review aims to provide up-to-date research progress on incorporating organic growth additives to enhance in vitro tissue culture protocols and to emphasize the importance of using PCR-based molecular markers such as RAPD, ISSR, SSR, and SCoT. The review was assessed based on the peer-reviewed works published in scientific databases including Science Direct, Scopus, Springer, JSTOR, onlinelibrary, and Google Scholar.